Evidence and evaluation in social policy - Greener, Ian.; Greve, Bent. (Chichester, West Sussex : Wiley Blackwell, 2014)
By examining the role of evidence in social policymaking and the extent of its influence, Evidence and Evaluation in Social Policy delves deeply into one of the central questions of the field for the last 20 years. Chronicles the trend towards evidence-based policy over the last decadeAssesses the ways in which scarce resources can best be used for the best care, particularly in times of austerityDescribes methodological innovation, the ways in which researchers and politicians are working together effectively, and suggestions for future improvement>
Research on Lone Parents not in Work under the Previous Labour GovernmentWhat Do We Know about Lone Parents not in Work after 13 Years of Research?; What Went Wrong?; The Role of Research and Researchers; Lessons for Evidence-based Policy-making; By Way of Conclusion: Why it Matters . . .; References; 8: Putting the Research Boot on the Policymakers' Foot: Can Participatory Approaches Change the Relationship between Policymakers and Evaluation?; Introduction; The Policy Process, Social Science and Politics; Participatory Research Approaches and Politics.
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Social policy -- Evaluation; Social planning -- Evaluation; Public welfare -- Evaluation; Politique sociale; Planification sociale; Aide sociale; SOCIAL SCIENCE -- General; Public welfare -- Evaluation; Social policy -- Evaluation; 2; Sociologi